2001
DOI: 10.1037/0278-7393.27.4.931
|View full text |Cite
|
Sign up to set email alerts
|

A demonstration and comparison of two types of inference-based memory errors.

Abstract: Participants viewed slides depicting ordinary routines (e.g., going grocery shopping) and later received a recognition test. In Experiment 1, there was higher recognition confidence to high-schema-relevant than to low-schema-relevant items. In Experiment 2, participants viewed slide sequences that sometimes contained a cause (e.g., woman taking orange from bottom of pile) but not an effect scene (oranges on floor), or an effect but not a cause scene. Participants mistook new cause scenes as old when they viewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 33 publications
4
68
1
Order By: Relevance
“…Recently, Hannigan and Reinitz (2001) showed that backward causal inferences sometimes cause participants to mistakenly "remember" scenes representative of those inferences. In that study, participants viewed episodes (e.g., going grocery shopping, attending a lecture) in which either a cause slide or an effect slide was presented.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Hannigan and Reinitz (2001) showed that backward causal inferences sometimes cause participants to mistakenly "remember" scenes representative of those inferences. In that study, participants viewed episodes (e.g., going grocery shopping, attending a lecture) in which either a cause slide or an effect slide was presented.…”
Section: Methodsmentioning
confidence: 99%
“…The sourcemonitoring framework is again useful in accounting for this result. Hannigan and Reinitz (2001) argued that the participants remembered the results of their inferences but failed to remember that the information had been internally generated. Instead, they interpreted the information as arising from externallywitnessed events(a type of sourcemonitoring failure referred to as reality-monitoringerrors by Johnson, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This use of prior knowledge in comprehension is central to Sanford and Garrod's (1998) scenario-mapping model (see also Schmalhofer, McDaniel, & Keefe, 2002). However, the knowledge on which the detection of causal relevance is based does not have to be of a full scenario, script, or schema (Hannigan & Reinitz, 2001). Glenberg and Robertson's (1999) indexical hypothesis explains the detection of causal relevance on the basis of more elementary knowledge for at least concrete events.…”
Section: Causal Relevancementioning
confidence: 99%
“…This interpretation was based on their knowledge of the physical world, in particular that part of their knowledge that is concerned with the way in which a force is transmitted from one physical object (officer Abrams) to another (Van Eck), the causal field of their intuitive theory of mechanics (tenet iii). 1 But the witnesses probably regarded this interpretation as a straightforward observation, as something they had actually seen and on which they only needed to report as faithfully as possible.Also, the police and the prosecution probably took their reports as factual evidence.How this can come about was aptly demonstrated by a recent experiment by Hannigan and Reinitz (2001). They showed subjects a series of slides of a woman shopping in a supermarket and at one point picking up an orange off the floor.…”
Section: Causal Analysis Of the Warmoesstraat Casementioning
confidence: 99%